2014
DOI: 10.1038/nature13919
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific clocks in Arabidopsis show asymmetric coupling

Abstract: Many organisms rely on a circadian clock system to adapt to daily and seasonal environmental changes. The mammalian circadian clock consists of a central clock in the suprachiasmatic nucleus that is tightly coupled and synchronizes other clocks in peripheral tissues1, 2. Plants also have a circadian clock, but plant circadian clock function has long been assumed to be uncoupled3. Only a few studies have been able to show a weak, local coupling among cells4, 5, 6, 7. Here, by implementing two novel techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
301
0
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(332 citation statements)
references
References 36 publications
13
301
0
18
Order By: Relevance
“…These results clearly indicate that P. hybrida plants likely possess circadian clocks that have different properties in flowers and leaves. Although tissue specificity of the circadian clock has been shown in Arabidopsis previously (33)(34)(35), current examples in other plant species are still limited (36). Of note is the fact that the common study organism for FVBP research, P. hybrida, is a hybrid of Petunia axillaris and Petunia integrifolia.…”
Section: Discussionmentioning
confidence: 99%
“…These results clearly indicate that P. hybrida plants likely possess circadian clocks that have different properties in flowers and leaves. Although tissue specificity of the circadian clock has been shown in Arabidopsis previously (33)(34)(35), current examples in other plant species are still limited (36). Of note is the fact that the common study organism for FVBP research, P. hybrida, is a hybrid of Petunia axillaris and Petunia integrifolia.…”
Section: Discussionmentioning
confidence: 99%
“…S6), suggesting that their difference in function could reflect an inherent difference in the activity of the two proteins. Alternatively, it is also possible that these broad expression patterns in whole leaves may not accurately reflect localized differences in expression in specific leaf tissues critical for their influence on flowering, as recently observed for a number of evening genes in the Arabidopsis clock (Endo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given that there are EE (AAAATATCT) and EE-like elements (AATATCT) in the COR27 promoter region (Mikkelsen and Thomashow, 2009) and that it was reported that the promoter of COR27 was occupied by CCA1 in a ChIP-seq analysis of plants expressing CCA1-GFP (Nagel et al, 2015), we measured transcription of COR27 and COR28 in the cca1 lhy double mutant. ACTIN7 (ACT7), ASPARTIC PROTEINASE A1 (APA1), and ISOPENTENYL PYROPHOSPHATE: DIMETHYLALLYL PYROPHOSPHATEISOMETASE2 (IPP2) (Endo et al, 2014) were used as internal controls for normalization in our qPCR analysis. Transcription of both COR27 and COR28 was upregulated in the cca1 lhy double mutant in the morning (ZT4 and ZT8) (Figures 5C and 5D;Supplemental Figures 7A to 7D) in LD conditions.…”
Section: Mutation Of Cor27 and Cor28 Enhances Freezing Tolerancementioning
confidence: 99%